Advertisement Remove all ads

Factorise x3 + 6x2 + 11x + 6 completely using factor theorem. - Mathematics

Sum

Factorise x3 + 6x2 + 11x + 6 completely using factor theorem. 

Advertisement Remove all ads

Solution

`"Let"  f(x)=x^3+6x^2+11x+6 `

`for=x=-1 `

`f(-1)=(-1)^3+6(-1)^2+11(-1)+6` 

`=-1+6-11+6=12-12=0 `

Hence, (x+1) is a factory of f(x) 

 

∴ `x^3+6x^2+11x+6=(x+1)(x^2+5x+6) `

                              =`(x+1)(x^2+2x+3x+6) `

                             =`(x+1)[x(x+2)+3(x+2)] `

                              =`(x+1)(x+2)(x+3)`

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Maths Class 10 ICSE
Chapter 8 Remainder and Factor Theorems
Exercise 8 (C) | Q 7 | Page 112
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×